Linear static response of model plasmas and Yukhnovsky-Kelbg-Deutsch effective potential - Adamyan, V.M.; Tkachenko, I.M. (Condensed Matter Physics, 2000)
A theory of transport coefﬁcients of fully ionized strongly coupled plasmas, based on the self-consistent ﬁeld concept and having no adjustable parameters, is presented. The proposed approach is not connected directly with the kinetic equation. A comparison of the obtained results with the computer simulation data on the classical hydrogen-like plasmas macroscopic properties shows that using the Yukhnovsky-Kelbg-Deutsch effective pair potentials instead of the genuine Coulomb potentials can compensate, to a certain extent, inaccuracies related to the standard approximations of the quantum theory of Coulomb systems.